Reading Asian American Literature : From Necessity to Extravagance - Wong, Sau-ling Cynthia (Book collections on Project MUSE., 2001)
A recent explosion of publishing activity by a wide range of talented writers has placed Asian American literature in the limelight. As the field of Asian American literary studies gains increasing recognition, however, questions of misreading and appropriation inevitably arise. How is the growing body of Asian American works to be read? What holds them together to constitute a tradition? What distinguishes this tradition from the "mainstream" canon and other "minority" literatures? In the first comprehensive book on Asian American literature since Elaine Kim's ground-breaking 1982 volume, Sau.